A cone beam CT-based study on fiducial seed migration and planning target volume margin in prostate radiotherapy. Issue 4 (21st December 2020) - Thuruthiyil, Divya K.; Cawley, Martin; Metwaly, Mohamed
Abstract: Aim: This study attempts to investigate fiducial marker (FM) migration and calculate the prostate planning target volume (PTV) margin considering the setup errors after translation corrections alone (T) and translation plus rotational corrections (T+R) and anatomy variation with respect to the corrected fiducial position, analysed on cone beam computed tomography (CBCT) images. Methods and materials: CBCT images from 25 patients are analysed for FM movements, setup error and anatomy variation with respect to the seed match positions. Systematic and random components of setup error and prostate movements are used to calculate the PTV margin for CBCT-based FM localisation in two scenarios, translation corrections only and translation plus rotational correction. MTNW887825 soft tissue gold markers (Civco, Orange City, FL, USA) were used with the department-specific immobilisation system and rectal and bladder filling protocols. Results: The average directional inter-marker distance variation is −0·05 ± 0·90 mm. The systematic setup errors for T+R are 0·40, 0·63 and 0·80 mm in right–left (RL), anterior–posterior (AP) and superior–inferior (SI), respectively. The corresponding values for T only are 0·54, 0·69 and 0·90 mm. The systematic prostate movement from T+R corrected FM positions are 0·65, 1·27 and 1·32 mm in the RL, AP and SI directions. Findings: Minimal FM movements are noted from the study. The PTV margins to incorporate the daily T+R corrected setup error and prostate deformation are found to be 2·5, 4·5 and 5·2 mm in the RL, AP and SI directions, respectively. The corresponding margins for T only corrected scenario are found to be 2·8, 4·8 and 5·7 mm.